GERAKAN DAKWAH ORGANISASI PERSATUAN ISLAM TIONGHOA INDONESIA (PITI) - alim, Aip Nur; Suparto, Suparto (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2025)
The missionary movement of the Indonesian Chinese Islamic Association (PITI) focuses on spreading Islamic values among the Chinese community in Indonesia. PITI seeks to integrate Chinese culture with Islamic teachings, thus creating harmony in diversity. Through various programs, such as religious studies, seminars, and social activities, PITI seeks to strengthen religious understanding, increase solidarity between communities, and make positive contributions to the wider community. This study aims to analyze the missionary movement carried out by the Indonesian Chinese Islamic Association (PITI) and its impact on the Chinese Muslim community in Indonesia. The research method used is a descriptive qualitative study with a case study approach, where data is obtained through in-depth interviews, observations, and literature reviews to obtain a comprehensive picture of the dynamics of PITI's missionary work. The results of the study indicate that PITI has an important role in increasing religious awareness among the Chinese community through structured and inclusive missionary programs. In addition, PITI also contributes to strengthening the religious and social identities of community members. The conclusion of this study highlights the importance of a missionary approach that is sensitive to local culture to achieve more effective results. Suggestions for similar future research are to explore the dynamics of interactions between the Chinese Muslim community and the majority society, as well as to evaluate more innovative da'wah strategies in diverse contexts. Abstrak Gerakan dakwah Organisasi Persatuan Islam Tionghoa Indonesia (PITI) berfokus pada penyebaran nilai-nilai Islam di kalangan komunitas Tionghoa di Indonesia. PITI berupaya mengintegrasikan budaya Tionghoa dengan ajaran Islam, sehingga menciptakan harmoni dalam keberagaman. Melalui berbagai program, seperti pengajian, seminar, dan kegiatan sosial, PITI berusaha untuk memperkuat pemahaman agama, meningkatkan solidaritas antarumat, serta memberikan kontribusi positif terhadap masyarakat luas. Penelitian ini bertujuan untuk menganalisis gerakan dakwah yang dilakukan oleh Organisasi Persatuan Islam Tionghoa Indonesia (PITI) dan dampaknya terhadap masyarakat Tionghoa Muslim di Indonesia. Metode penelitian yang digunakan adalah studi kepustakaan (library research), dimana data dikumpulkan dari buku dan jurnal. Hasil penelitian menunjukkan bahwa PITI memiliki peran penting dalam meningkatkan kesadaran beragama di kalangan komunitas Tionghoa melalui program dakwah yang terstruktur dan inklusif. Selain itu, PITI juga berkontribusi dalam memperkuat identitas keagamaan dan sosial anggota komunitas. Kesimpulan dari penelitian ini menyoroti pentingnya pendekatan dakwah yang sensitif terhadap budaya lokal untuk mencapai hasil yang lebih efektif. Saran untuk penelitian serupa di masa mendatang adalah untuk mengeksplorasi dinamika interaksi antara komunitas Tionghoa Muslim dengan masyarakat mayoritas, serta mengevaluasi strategi dakwah yang lebih inovatif dalam konteks yang beragam.